Use of Selective Pulmonary Vasodilators to Treat Pulmonary Arterial Hypertension Prior to Successful Surgical Closure of Atrial-Level Shunts - MD, Yuli Y. Kim; MD, Stephanie Fuller; MD, Benjamin D’Souza; MD, Yoshiya Toyoda; MD, Paul Forfia (Archives of Clinical and Medical Case Reports, 2020)
Background: Significant pulmonary hypertension [PH] is often considered a contraindication for closure of atrial septal defects [ASD]. Treatment of pulmonary arterial hypertension [PAH] with selective pulmonary vasodilators can allow for surgical repair of ASD otherwise considered prohibitive. We describe our experience in the assessment and treatment of adults with ASD and PAH with pulmonary vasodilator therapy who underwent successful surgical repair. Methods: Retrospective case series of patients with atrial level shunts and significant PAH who met clinical criteria for repair. Clinical and demographic data were collected through review of the electronic medical records. Echocardiographic data were analyzed by a single cardiologist. Results: Four patients with ASD and PAH were identified. All four patients experienced a decrease in pulmonary vascular resistance and increase in shunt fraction with institution of PH-directed therapy. Each underwent successful surgical repair with improvements in six-minute walk distance, right ventricular systolic function, and natriuretic peptide levels. All patients remained improved and stable on PH medications at last follow-up. Conclusion: With appropriate selection and application of therapy, patients with atrial level shunts and severe PAH can successfully undergo surgical closure following medical treatment of their pulmonary arterial hypertension.